(untitled) (Bangladesh Medical Journal, 2019)
Nonalcoholic fatty liver disease (NAFLD) is a metabolic disorder characterized by excessive triglyceride accumulation in hepatocytes. NAFLD has a multifactorial etiology and a combination of environmental, genetic and metabolic factors play a role in the development of advanced disease. NAFLD consists of a wide spectrum of conditions, ranging from simple steatosis to nonalcoholic steatohepatitis (NASH) which can progress to cirrhosis and hepatocellular carcinoma (HCC). Despite the high prevalence and severity of hepatic illness, NAFLD remains underdiagnosed, because of few symptoms, lack of accurate laboratory markers. The accurate diagnosis of NASH remains dependent on specific histological parameters in liver biopsy. Although liver biopsy remains the ‘gold standard’, there are practical limitations, including costs and risks. There is an increasing requirement for simple, less invasive, highly accurate and affordable screening tools. Aspartate aminotransferase (AST) has been proposed as a noninvasive and available marker for assessment of NASH. A hospital based observational study was carried out for a period of two years in the Department of Hepatology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. Data were analyzed by SPSS version 16. Qualitative and quantitative data were analyzed by Chi-square test and student’s t-test respectively. Fifty (50) patients were analysed. Twenty five were NASH and twenty five were non- NASH. AST in NASH group were 55.2 ± 30.1 IU/L and in Non-NASH group were 33.6± 20 IU/L. In NASH group significantly higher percentage of raised AST had NASH compared with normal AST (68% vs.32%).There was significant difference in the NAFLD activity score for diagnosing NASH between elevated and normal AST (P value 0.004). Higher AST values correlated with higher specificity. By multivariate analysis AST were found to be significant. Thus Aspartate aminotransferase (AST) is a good predictor for diagnosing non- alcoholic steatohepatitis (NASH). Bangladesh Med J. 2019 Jan; 48 (1): 44-49